Critical Failure Factors in Selling Shoplots towards Sustainability of New Township Development - Tawil, N.M.; Mohamad, N.I.; Usman, I.M.; Tahir, M. M.; Othuman Mydin, M.A. (EDP Sciences, 2014)
The focus of this research is to identify the critical factors of shop houses sale failure in Nilai New Township. The critical factors of sale failure of commercial property types, shop houses in new township need to be discover as reported by Valuation and Property Services Department (JPPH) showed 5,931 units of shop houses in Malaysia is currently completed but remained unsold where Johor was recorded as the highest with unsold units followed by Negeri Sembilan. Thus Nilai New towship is chosen as research sample for unsold shop houses units due to its strategic location which is near to KLIA, International Sepang Circuit, educational instituitions and surrounded by housing scheme but yet still has numbers of unsold units. Data was gathered from survey question between developers, local authority, purchasers/tenant and local residents.. Generally, the factors of sale failure are economy, demography, politic, location and access, public and basic facilities, financial loan, physical of product, current stock of shop houses upon completion, future potential of subsale and rental, developer’s background, promotion and marketing, speculation and time.